2020
DOI: 10.4490/algae.2020.35.2.28
|View full text |Cite
|
Sign up to set email alerts
|

Feeding by common heterotrophic protist predators on seven <italic>Prorocentrum</italic> species

Abstract: Species belonging to the dinoflagellate genus Prorocentrum are known to cause red tides or harmful algal blooms. To understand the dynamics of a Prorocentrum sp., its growth and mortality due to predation need to be assessed. However, there are only a few Prorocentrum spp. for which heterotrophic protist predators have been reported. We explored feeding by the common heterotrophic dinoflagellates Gyrodinium dominans, Oxyrrhis marina, Pfiesteria piscicida, Oblea rotunda, and Polykrikos kofoidii and the naked ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 91 publications
0
6
0
Order By: Relevance
“…Marine dinoflagellates are ubiquitous and a major component of marine ecosystems (Hallegraeff 1993, Taylor et al 2008, Klueter et al 2017. They play diverse roles in marine food webs (Hansen 1991, Jeong et al 2010, Anderson and Menden-Deuer 2017, You et al 2020a; autotrophic dinoflagellates grows photosynthetically (Jang et al 2017a). Among the 11 heterotrophic protists explored, there were no potential predators that were able to feed on actively swimming Y. yeosuensis cells, which escaped via rapid jumps (Jeong et al 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…Marine dinoflagellates are ubiquitous and a major component of marine ecosystems (Hallegraeff 1993, Taylor et al 2008, Klueter et al 2017. They play diverse roles in marine food webs (Hansen 1991, Jeong et al 2010, Anderson and Menden-Deuer 2017, You et al 2020a; autotrophic dinoflagellates grows photosynthetically (Jang et al 2017a). Among the 11 heterotrophic protists explored, there were no potential predators that were able to feed on actively swimming Y. yeosuensis cells, which escaped via rapid jumps (Jeong et al 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…Cells of L. masanensis and P. piscicida are known to feed on dinoflagellate prey species of ≤9.7 µm in the equivalent spherical diameter (ESD) and athecate dinoflagellates such as Margalefidinium polykrikoides, Akashiwo sanguinea, and Gymnodinium catenatum, but they did not feed on thecate dinoflagellates ≥12.1 µm (Jeong et al 2007). You et al (2020) reported that P. piscicida fed on larger sized thecate dinoflagellates, but only on motionless cells. Thus, the present study is the first to report that L. masanensis and P. piscicida are able to feed on a moving thecate dinoflagellate ≥12.1 µm because the ESD of T. furca is approximately 29 µm (Jeong et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Using the same calculation, the carbon contents of all predator species in the present study were also evaluated from the cell volume. The cell volumes of the heterotrophic predators were assessed using the methods of Jang et al (2016) for A. glandula; Ok et al 2017for G. shiwhaense; Kang et al (2020) for G. dominans, G. jinhaense, and G. moestrupii;Jeong et al (2007) for L. masanensis and P. piscicida; You et al (2020) for O. rotunda and O. marina; and this study for Rimostrombidium sp. (Table 1).…”
Section: Introductionmentioning
confidence: 92%
“…Gjin Gmoe Chl-a T S highest abundance of each species was found during the study period was 127.0, 6.8, and 0.9 ng Chl-a mL -1 for G. dominans, G. jinhaense, and G. moestrupii, respectively. Assuming that the ratio of carbon to Chl-a was 40 (Peterson and Festa 1984) and all Chl-a were attributed to P. donghaiense, using the equation of You et al (2020), the calculated growth rate of G. dominans on P. donghaiense at 127 ng Chl-a mL -1 (5,080 ng C mL -1 ) would be 1.09 d -1 . Similarly, if all Chl-a belonged to D. salina, using the equation of Kang et al (2020), the calculated growth rate of G. jinhaense on D. salina at 6.8 ng Chl-a mL -1 (270 ng C mL -1 ) would be 0.20 d -1 .…”
Section: Species Gdomentioning
confidence: 99%